2021
DOI: 10.1002/bco2.81
|View full text |Cite
|
Sign up to set email alerts
|

Oncological outcomes of dose reductions in cisplatin due to renal dysfunction for patients with metastatic urothelial carcinoma

Abstract: Objective To investigate whether dose reductions in cisplatin due to renal dysfunction were associated with worse clinical outcomes in metastatic urothelial carcinoma (UC) patients. Patients and methods One hundred and fifty one metastatic UC patients who received first‐line gemcitabine plus cisplatin (GC) salvage chemotherapy without a previous history of peri‐surgical chemotherapy were included in this retrospective study. Patients with endogenous creatinine clearance of 60 mL/min or more were treated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Overall, the oncologic outcomes appear safe, and rendering patients hypogonadal was rare. See Ory's Figure 3 for a management algorithm—especially useful for non‐palpable masses that may be benign. To the clinic… For papers helping us with clinical utility, we have an original study by Murakami et al 2 on 151 patients with metastatic urothelial carcinoma. This examined whether cisplatin reductions due to renal dysfunction would affect oncologic outcomes and found that they did not.…”
Section: Figurementioning
confidence: 99%
“…Overall, the oncologic outcomes appear safe, and rendering patients hypogonadal was rare. See Ory's Figure 3 for a management algorithm—especially useful for non‐palpable masses that may be benign. To the clinic… For papers helping us with clinical utility, we have an original study by Murakami et al 2 on 151 patients with metastatic urothelial carcinoma. This examined whether cisplatin reductions due to renal dysfunction would affect oncologic outcomes and found that they did not.…”
Section: Figurementioning
confidence: 99%